2021
DOI: 10.1097/inf.0000000000003149
|View full text |Cite|
|
Sign up to set email alerts
|

Multisystem Inflammatory Syndrome in Infants <12 months of Age, United States, May 2020–January 2021

Abstract: Background: Multisystem inflammatory syndrome in children (MIS-C), temporally associated with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has been identified in infants <12 months old. Clinical characteristics and follow-up data of MIS-C in infants have not been well described. We sought to describe the clinical course, laboratory findings, therapeutics and outcomes among infants diagnosed with MIS-C. Methods: Infants of age <12 months with MIS-C were identified by reports to the CDC's MIS-C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
2
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 21 publications
0
48
2
1
Order By: Relevance
“…The majority of studies reporting long-term follow-up of children with MIS-C are from developed countries, 10 16 and there is lack of such data from the Indian subcontinent. In this retrospective study from North India, we described the follow-up of 34 children with MIS-C who were admitted during the first wave of SARS-CoV-2 infection and demonstrated that majority of the children were asymptomatic and myocardial dysfunction and coronary artery changes resolved in majority during follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of studies reporting long-term follow-up of children with MIS-C are from developed countries, 10 16 and there is lack of such data from the Indian subcontinent. In this retrospective study from North India, we described the follow-up of 34 children with MIS-C who were admitted during the first wave of SARS-CoV-2 infection and demonstrated that majority of the children were asymptomatic and myocardial dysfunction and coronary artery changes resolved in majority during follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Information on the long-term outcome of MIS-C is limited to a few studies from developed countries. 10 16 Therefore, we planned this follow-up study to describe the clinical features, echocardiographic findings, and long-term outcome of children with MIS-C from a tertiary care center in North India.…”
Section: Introductionmentioning
confidence: 99%
“…CRP is a sensitive marker of inflammation even in neonates [ 8 , 9 ] so we hypothesize a lower level of measurable inflammation in infants compared to older children admitted with COVID-19, but it may reflect admission of infants with milder disease. Less inflammation might partially explain why infants accounted for only 4% of MIS-C cases in a large series [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The signs and symptoms of MIS-C include fever, abdominal pain, vomiting, diarrhea, skin rash, mucocutaneous lesions, hypotension, and cardiovascular and neurologic compromise [ 33 ]. Reviews of complications secondary to MIS-C have been described elsewhere [ 34 , 35 ].…”
Section: Multisystem Inflammatory Syndrome In Children (Mis-c)mentioning
confidence: 99%